2018
DOI: 10.1177/1528083718798637
|View full text |Cite
|
Sign up to set email alerts
|

Development of nonwoven automotive carpets made of recycled PET fibers with improved abrasion resistance

Abstract: In this study, velour design molded automotive carpets made of recycled polyethylene terephthalate (PET) fibers were developed via needle-punching process to improve their abrasion resistance properties. Initially, virgin PET fibers and recycled PET (rPET) fibers derived from PET bottle wastes were supplied from different producers and they were tested in terms of their fiber properties such as fiber length, crimp, tensile strength, elongation, tenacity, and intrinsic viscosity. It was demonstrated that recycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Nonwoven fabrics (Atakan et al 2018) 2 -The optimal composition selected contained 85% recycled PET and 15% bicomponent PET, which suggested that it could be used instead of 80% virgin PET and 20% bicomponent PET. 2 -In general, fibers with longer lengths showed better abrasion resistance in the final product.…”
Section: Recycled Pet Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonwoven fabrics (Atakan et al 2018) 2 -The optimal composition selected contained 85% recycled PET and 15% bicomponent PET, which suggested that it could be used instead of 80% virgin PET and 20% bicomponent PET. 2 -In general, fibers with longer lengths showed better abrasion resistance in the final product.…”
Section: Recycled Pet Fibersmentioning
confidence: 99%
“…very wide, such as sound absorber (Özkal and Cengiz Çallıoğlu 2020), apparel (Anderson 2005), medical textiles (Mothilal et al 2019), automotive textiles (Atakan et al 2018), filters (Chauhan et al 2019), sanitary masks (Opálková Šišková et al 2020), and packaging (Lin et al 2018).…”
Section: Recycled Pet Fibersmentioning
confidence: 99%
“…Atakan et al investigated the abrasion resistance characteristics of needle-punched automotive nonwoven carpets made from virgin and recycled PET fibers. They reported that the quality levels of needle-punched automotive carpet produced with recycled PET fibers are comparable to virgin PET fibers (Atakan et al, 2018). Trajkovic et al analyzed the mechanical properties of nonwoven fabrics developed from recycled polyester fibers for geotextiles applications.…”
Section: Rjta 252 158mentioning
confidence: 99%
“…Yüksekkaya et al 11 investigated the properties of open-end rotor yarns and single-jersey fabrics from virgin cotton, recycled cotton, virgin PES, recycled PES fibers, and blends of these fibers. Atakan et al 12 focused on improving abrasion resistance of otomotive carpets made from r-PET fibers. The results show that use of 85% r-PET/15% bicomponent PET had almost equal performance in terms of both fiber loss and carpet appearances with carpets consisting of 80% PET/20% bicomponent PET.…”
Section: Introductionmentioning
confidence: 99%